A new norm-relaxed SQP algorithm with global convergence - Zheng, Hai-Yan; Jian, Jin-Bao; Tang, Chun-Ming; Quan, Ran (Applied mathematics letters, 2010)
A new norm-relaxed sequential quadratic programming algorithm with global convergence for inequality constrained problem is presented in this paper, and the quadratic programming subproblem can be solved at each iteration. Without the boundedness assumptions on any of the iterative sequences, the global convergence can be guaranteed by line search with l ∞ penalty function and under some mild assumptions.